An Elaboration of Service Views within the UAF. Issue 1 (20th September 2021) - Hause, Matthew; Kihlström, Lars‐Olof
Abstract: Services in the Unified Architecture Framework (UAF) are not just software services. Services can include transport, surveillance, communications, providing healthcare and medical services, etc. The UAF implements DoDAF using the Systems Modeling Language (SysML) as well as the British MODAF and NATO NAF. The DoDAF Service views implement services by duplicating the systems views and labeling the systems elements as services. This causes some confusion with engineers who either implement solution‐based service views or ignore them completely. Even when implemented, they can cause confusion in the model as it becomes difficult to tell if a model element describes a service or a system implementing a service. The UAF implementation of the MODAF services views provides a distinct set of views, concepts and traceability. The Service Oriented Views do not specify how the service is to be implemented, but the requirements for the services. The Resources (Systems) Views implement services in various phases and their deployment will modify the configurations of the system at the very highest level. This paper will show how services views trace from capabilities and how that can be used to define system resource requirements.